Analisis Pengendalian Kualitas dengan Metode PDCA dan RCA untuk Menurunkan Cacat Produk Sepatu di PT. XYZ - Ilma Nur Hikmah; Ade Ima Afifa Himayati; Cikita Berlian Hakim (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The high level of product defects in the manufacturing industry can reduce product quality and increase production costs due to repeated repair processes. This study aims to identify the dominant types of defects, analyze the factors that cause the defects, and prepare proposals for quality improvements in the shoe production process at PT. XYZ uses the PDCA (Plan-Do-Check-Act) and RCA (Root Cause Analysis) methods. This study uses a mixed methods approach with a sample of product defect data in the January-June 2025 period. Data was obtained through observation, interviews, documentation, and check sheets. The analysis was carried out using pareto diagrams, fishbone diagrams, and the 5W+1H approach. The results showed that the dominant defects were bonding or glue not sticking by 27% and untidy stitches by 20%. The main factors that cause disability are due to humans, machines, methods, materials, and the work environment. The implementation of the repair resulted in a reduction in bonding defects by 25.93% and untidy stitches by 27.78%. Companies are advised to standardize work processes, train operators, maintain machinery regularly, and improve quality control to support continuous improvements.